2012
DOI: 10.2147/opth.s35122
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of persistent corneal erosion after administration of topical rebamipide

Abstract: Rebamipide is an antiulcer agent used to treat gastric ulcer and gastritis. Biological effects of rebamipide include cytoprotection, wound healing, and anti-inflammatory properties that are known to be universal for a variety of tissues in addition to gastrointestinal mucosa. The therapeutic effects of rebamipide eye drops are due to its ability to increase corneal and conjunctival mucin-like substances and improve corneal and conjunctival injury in vivo. In this paper, we report a case of Sjögren’s syndrome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…Application of rebamipide has been shown to increase the proliferation of goblet cells in eye disorders. 26,27 We also identified that rebamipide increases goblet cell proliferation in the normal colon through H&E and PAS staining (Fig. 3a,b).…”
Section: Resultsmentioning
confidence: 70%
“…Application of rebamipide has been shown to increase the proliferation of goblet cells in eye disorders. 26,27 We also identified that rebamipide increases goblet cell proliferation in the normal colon through H&E and PAS staining (Fig. 3a,b).…”
Section: Resultsmentioning
confidence: 70%
“…In addition, a clinical trial recently revealed that rebamipide ameliorated corneal and conjunctival epithelial damage as well as increasing tear film stability in individuals with dry eye 12. Rebamipide is thus now marketed in Japan as a preservative-free ophthalmic suspension for the treatment of dry eye 13. Given that inflammation has been implicated in the pathology of dry eye, the anti-inflammatory effects of rebamipide might contribute to its efficacy for the treatment of dry eye.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the clinical effects of rebamipide eye drops (Mucosta® ophthalmic suspen sion UD2%; Otsuka Pharmaceutical Co, Ltd, Tokyo, Japan) for various types of dry eye were reported 1,2,23,24. Rebamipide eye drops for dry eye are also being developed for approval in the US.…”
Section: Introductionmentioning
confidence: 99%